Enhancing Fullerene-Based Solar Cell Lifetimes by Addition of a Fullerene Dumbbell - Zhe Li (Angewandte Chemie International Edition, 2014)
Cost-effective, solution-processable organic photovoltaics (OPV) present an interesting alternative to inorganic silicon-based solar cells. However, one of the major remaining challenges of OPV devices is their lack of long-term operational stability, especially at elevated temperatures. The synthesis of a fullerene dumbbell and its use as an additive in the active layer of a PCDTBT:PCBM-based OPV device is reported. The addition of only 20 % of this novel fullerene not only leads to improved device efficiencies, but more importantly also to a dramatic increase in morphological stability under simulated operating conditions. Dynamic secondary ion mass spectrometry (DSIMS) and TEM are used, amongst other techniques, to elucidate the origins of the improved morphological stability.